Perspectiva dos profissionais de saúde sobre cuidados paliativos na reabilitação em saúde - Almeida, Brenda Natallie Girardi de (2024)
The objective of this research was to investigate and analyze the perception of health professionals who work in Specialized Rehabilitation Centers regarding the possibilities of articulation between Palliative Care and Health Rehabilitation. The specific objectives are: to characterize the health professionals of the Centers Specialized in Rehabilitation, map health professionals' understanding of the relationship between palliative care and health rehabilitation and; identify professionals' adherence to a palliative care proposal within Specialized Rehabilitation Centers. This is a field study, descriptive, with a qualitative approach. The research territory consists of three rehabilitation reference centers located in the interior of Rio Grande do Sul. Data collection occurred through the focus group technique, which was applied in each of the institutions. Sampling is non-probabilistic and for convenience, so that 9 professionals participated in the focus group at the first institution, 5 professionals participated in the focus group at the second institution and 7 professionals participated in the focus group at the third institution. In all groups, diversity of professional categories was guaranteed. Data analysis took place through content analysis. This research presents its results in an article entitled "The (im)possibility of articulation between Palliative Care and Rehabilitation". The article presents the professionals' conception of palliative care and their perceptions about the possibilities and impossibilities of articulation between palliative care and rehabilitation.